Contextual-Based Interactive Learning Media on Indonesian Language Learning Outcomes for Vocabulary in Grade II Elementary School - KD Yuna Maha Dewita; I Gede Astawan; Ni Ketut Desia Tristiantari (Jurnal Media dan Teknologi Pendidikan, 2026)
Elementary school students’ vocabulary mastery remains relatively low due to the dominance of conventional teaching methods and the limited use of interactive learning media that align with the characteristics of lower-grade students. This condition results in low student engagement and suboptimal learning outcomes in Indonesian language learning, particularly in vocabulary instruction. This study aims to develop contextual-based interactive learning media and to determine its validity, practicality, and effectiveness in improving second-grade students’ Indonesian vocabulary learning outcomes. The study employed the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation questionnaires, practicality questionnaires, observations, and learning outcome tests in the form of pretests and posttests. The results indicate that the developed contextual-based interactive learning media has a very high level of validity, is considered practical by teachers and students, and is effective in improving students’ vocabulary learning outcomes, as evidenced by higher posttest scores compared to pretest scores. In conclusion, the contextual-based interactive learning media is feasible for use as an alternative instructional medium in Indonesian language learning. The findings imply that the integration of contextual and interactive media can enhance learning quality, student engagement, and vocabulary learning outcomes in elementary education.